The development of instruction model to promote the problem solving skill thinking of vocational students based on theory of constructionism - ทวีเจริญกิจ, วรัตถ์พัชร์; สุรัชเรืองชัย, วิชิต (Ratchaphruek Journal, 2019)
The purpose of this research was to develop of instruction model to promote the problem solving skill thinking of vocational students based on theory of constructionism. The samples were 34 students of Samutprakarn Technical College in the first year in academic year 2015, selected by purposive sampling technique. The research instruments consisted of 1) the instruction model to promote and create in thinking for problem solving of vocational students based on theory of constructionism, 2) the lesson plans through the development of instruction model, and 3) the creative thinking for problem solving test the analyzing statistic was percentages, mean standard deviation and t-test independence The result of this research found that: 1) The instruction model to promote the problem solving skill thinking of vocational students based on theory of constructionism was developed, it consisted of 5 majors’ components principles, objectives, contents, instruction process and evaluation. The instruction process are 7 steps; 1) problem identify, 2) analysis problem, 3) selection problem, 4) decision phase, 5) implementation phase, 6) assessment, and 7) knowledge management. 2) The average scores of the create thinking for problem solving test after learning through the developed model was higher at 0.5 level of significance.